Narrative Storytelling in the Poetry of Ibn al-Rumi (d. 283 AH) - Aliwi, Prof. Najlaa Abdul-Hussain; Shihab, A.L. Ashjan Mahmoud (International Journal Of Literature And Languages, 2026)
Ibn al-Rumi, belonging to the Abbasid era, is among the most distinguished poets historically. The poet developed his singularity due to his fascination with the way experimentation appears in poetic imagery. The text involves a narrative structure within the poetry, and the broad domain of the work reflects the artist’s idea of the connection between innovation and humanity. The excellent and beautiful Ibn al-Rumi poetry contains various elements of art, such as imagery and structure, as well as the principles, for instance, experimentation and innovation. His poetry was characterized by its remarkable ability of transforming into vibrant, lifelike scenes, utilizing figurative techniques that blend meticulous psychological insights with a profound analytical tendency, which granted his poems a clear dramatic character, and one of the most prominent artistic features that capture the scholar’s attention in his poetry is the presence of the poetic tale as an expressive tool that transcends the boundaries of traditional lyricism, as the poet resorts to constructing narrative scenes that includes characters, events, and dialogues, thereby transforming the poetic text into a narrative space pulsating with movement. These narratives weren't just artistic decoration, but also expressive of his vision of reality, and a way to reveal the contradictions of Abbasid society, the social and psychological phenomena that surrounds it. And the importance of the narrative in his poetry is manifested in its ability to embody the poetic stance in a vivid manner, since it serves as a density where multiple voices overlap and meanings are intricately woven together. The tale also reveals the poet’s tendency for detail and accuracy in observation. Such intricate detailing underscores the poet’s contemplative essence and his rigorous analytical mind. This is where were delving into the narrative element of Ibn al-Rumi's work becomes an essential gateway to deciphering his aesthetic architecture and intellectual depth, it effectively peels back the layers of how storytelling was structured within the framework of classical Arabic verse. This study aims to map out these narrative occurrences, dissecting their artistic makeup and semantic roles to illustrate how they define his particular stylistic identity. Structurally, the research opens with a conceptual exploration of the 'Narrator' (Rawi) both linguistically and terminologically before bifurcating into two core investigations: the first identifies the foundational elements of the tale, while the second probes its distinctive traits in Ibn al-Rumi’s corpus, ultimately synthesizing the most vital conclusions.